Prevalence and Antibiotic Sensitivity Pattern of Pseudomonas Aeruginosa Isolates from Urine Samples in A Tertiary Care Hospital - Sharmin, Sohely; Nahar, Azizun; Alamgir, Farhana; Fahim, Imran (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Urinary tract infection (UTI) is one of the leading causes of infection worldwide. P. aeruginosa is a versatile opportunistic pathogen and it is the third most common organism causing nosocomial urinary tract infections. With the widespread use of antibiotics, multidrug resistance pseudomonas continues to go up rapidly. This multidrug resistance pseudomonas increases the risk of mortality and morbidity. Objective: To determine the prevalence of P. aeruginosa and to understand the current statistics of its antimicrobial resistance pattern. Methods: This retrospective study was conducted from January 2019 to December 2020 in the Department of Microbiology, Bangladesh Medical College Hospital, Dhaka. Clean catch mid-stream urine samples were collected in sterile containers. The samples were cultured on CLED agar media with a standard calibrated loop and incubated at 370C overnight. P. aeruginosa grows well at 25°C to 37°C, and its ability to grow at 42°C helped to distinguish it from other Pseudomonas species. Antibiotic sensitivity test was done according to Clinical and Laboratory Standard Institute (CLSI) guideline. Results: A total of 10427 urine sample were received in the department of Microbiology of BMCH during these two years. Isolation rate of P. aeroginosa was 4% in 2019 and it increased to 6% in 2020. Piperacillin/Tazobactam showed sensitivity which was 63.33% in 2019 and 82% in 2020, followed by imipenem, meropenem, amikacin, ciprofloxacin, ceftazidime and aztreonam; which were 50% to 60% on an average. Sensitivity of the organism to Gentamycin (13.33% in 2019 & 30.3% in 2020), Netilmicin (20% in 2019 & 30.3% in 2020) and Ceftriaxone (13.33% in 2019 & 12.3% in 2020) was found very low. Conclusion: P. aeruginosa isolates in urine culture is increasing in hospital admitted patient and becoming resistant to multiple antibiotics which is frightening. DS (Child) H J 2021; 37(1): 40-44